From a “Yugoslav Siberia”. The Difficulties of the Patriarchal Monastery of Peć 1919–1929 - Uroš Miketić (Токови историје, 2020)
The author has tried to outline the problems that the Patriarchal Monastery of Peć faced in the period 1919–1929. The heuristic background of the paper is primarily based on the documents stored in the Yugoslav Archives. It is mainly about the correspondence between the church and the relevant state authorities, which testifies to the fact that the central authorities had little understanding about the importance of this monastery for the survival of the Serbian people in Southern Serbia. That is why, the results of its policy toward the monastery were only partially achieved, similarly to other cases of this insufficiently integrated Yugoslav (Serbian) territory.